A method for improving the performance of Cu-SSZ-39 and a metal composite oxide-supported Cu-SSZ-39 catalyst
By supporting composite oxides of metals such as cerium, manganese, iron and other metals on the surface of Cu-SSZ-39 catalyst, the problem of lower activity and insufficient low-temperature activity in the hydrothermal aging process is solved, and the low temperature of the catalyst is achieved Improved activity, enhanced hydrothermal stability and improved anti-SO2 poisoning ability.
Patent Information
- Application Number
- CN202410100665.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-25
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-01-25
AI Technical Summary
The activity of Cu-SSZ-13 catalyst decreases during hydrothermal aging, and the low-temperature catalytic activity is insufficient, making it difficult to meet the requirements of the latest emission regulations.
The surface of the Cu-SSZ-39 catalyst is supported with composite oxides of metals such as cerium, manganese, and iron. The metal composite oxides are uniformly dispersed by equal volume impregnation method to improve the low-temperature activity and hydrothermal stability of the catalyst.
It significantly improves the low-temperature activity of Cu-SSZ-39 catalyst, widens the catalytic temperature window, enhances hydrothermal stability and anti-SO2 poisoning ability, and is suitable for nitrogen oxide treatment of tail gas of mobile source diesel engines.
Smart Images

Figure CN117983288B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for improving the performance of Cu-SSZ-39, in particular to a method for improving the NH3-SCR catalytic activity, hydrothermal stability and SO2 tolerance of Cu-SSZ-39, and also to a metal composite oxide-loaded Cu-SSZ-39 catalyst with good NH3-SCR catalytic performance, hydrothermal stability and sulfur poisoning resistance, belonging to the technical field of catalysts. Background Art
[0002] Nitrogen oxides (NO x ) as the main air pollutant, it will cause serious environmental problems such as photochemical smog and acid rain and cause great harm to human health. NH3 selective catalytic reduction (NH3-SCR) technology is a mature and effective NO x Removal technology is widely used in mobile source exhaust purification. The core of NH3-SCR technology is the catalyst. The development of catalysts with excellent catalytic activity, high hydrothermal stability, and high water and sulfur resistance is of great significance to the development of NH3-SCR technology.
[0003] Vanadium-tungsten-titanium catalyst (V2O5-WO3 / TiO2), as a commercial NH3-SCR catalyst for my country's National IV and National V stages, can no longer meet the latest emission regulations due to its narrow active temperature window, volatility, and biotoxicity. In recent years, Cu-SSZ-13 has been widely used due to its good catalytic activity and hydrothermal stability. However, the SCR system is placed at the rear end of the DPF (diesel particulate filter). When the DPF is regenerated, the catalyst is inevitably exposed to high-temperature steam, which will cause the molecular sieve framework to dealuminate and the active Cu species to migrate and aggregate, resulting in a sharp drop in the NH3-SCR activity of the Cu-SSZ-13 molecular sieve catalyst.
[0004] Therefore, people are not only committed to improving the hydrothermal stability of Cu-SSZ-13, but also to finding other molecular sieve carriers with better stability. Moliner et al. first used N, N-dimethyl-3, 5-dimethylpiperidinium hydroxide as a template to synthesize Cu-SSZ-39 (AEI structure) in 2012, and found through a series of characterization tests that it can stabilize Cu 2+ Species, avoiding dealumination and copper ion migration during hydrothermal aging, has extraordinary hydrothermal stability. However, compared with Cu-SSZ-13, its low-temperature activity is lacking. To address the above problems, researchers modified Cu-SSZ-39 to improve its NH3-SCR catalytic activity and SO2 tolerance.
[0005] Adding metal ions as additives to Cu-SSZ-39 is an effective way to improve the performance of Cu-SSZ-39, but metal ions as additives will compete for the ion exchange sites of Cu and reduce other properties of Cu-SSZ-39. For example, Lin et al. found that Y 3+ The introduction of 2+ and skeleton structure, significantly improving the hydrothermal stability of Cu-SSZ-39 catalyst. Wang et al. 3+ / Mn 2+ The redox property and surface acidity of the catalyst are enhanced, thereby improving the activity and hydrothermal stability of Cu-SSZ-39. However, the introduction of impurity ions will compete with the Cu active sites for ion exchange sites. For SSZ-39 with a higher silicon-aluminum ratio, because it has fewer ion exchange sites, the introduction of impurity ions may reduce the catalytic performance. CN201710100057 discloses a Cu-SSZ-39 catalyst doped with an additive. The effect is most obvious when the additive metal is Zr. The catalytic activity of the prepared catalyst (Zr loading 1.5 wt.%) is improved at low temperature and hydrothermal stability, but its temperature window is still narrow after hydrothermal aging (T 90 The range is 250 ~ 450 ° C). CN202011595255 discloses a Cu-SSZ-39@SSZ39 core-shell molecular sieve catalyst with a core-shell structure, which has high hydrothermal stability, but the low-temperature activity of the catalyst is not ideal and still needs to be improved. CN202110170135 discloses a Cu-SSZ-39@Cu-SSZ-13 composite molecular sieve with a core-shell structure, which can cover an extremely wide temperature window in both low and high temperature regions and has excellent hydrothermal stability, but the catalyst preparation process is relatively cumbersome and difficult to achieve widespread industrial application. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for improving the performance of Cu-SSZ-39, which loads metal composite oxides on Cu-SSZ-39 to improve the NH3-SCR catalytic activity, hydrothermal stability and SO2 tolerance of Cu-SSZ-39.
[0007] The specific technical solutions of the present invention are as follows:
[0008] A method for improving the performance of Cu-SSZ-39 is provided. The method is to load a metal composite oxide onto the surface of Cu-SSZ-39 to improve the performance of Cu-SSZ-39.
[0009] Furthermore, the metal in the metal composite oxide is any two or three of cerium, manganese and iron, that is, the metal in the metal composite oxide can be cerium manganese, ferrocerium, ferromanganese, or cerium ferromanganese.
[0010] Furthermore, when the metal in the metal composite oxide is cerium and manganese, the molar ratio of cerium to manganese is 1-3:1, for example, 1:1, 2:1, 3:1.
[0011] Furthermore, when the metal in the metal composite oxide is ferrocerium, the molar ratio of cerium to iron is 1-3:1, for example, 1:1, 2:1, 3:1.
[0012] Furthermore, when the metal in the metal composite oxide is manganese iron, the molar ratio of manganese to iron is 1:1-3, such as 1:1, 1:2, 1:3.
[0013] Furthermore, when the metal in the metal composite oxide is cerium-manganese-iron, the molar ratio of cerium, manganese and iron is 1-3:1:1-3, for example, 1:1:1, 2:1:1, 3:1:1, 1:1:3.
[0014] Preferably, when the metal in the metal composite oxide is cerium-manganese-iron, that is, when the metal composite oxide is cerium-manganese-iron composite oxide, the performance of Cu-SSZ-39 is better improved. More preferably, the molar ratio of cerium, manganese and iron is 3:1:1. Within this preferred range, the low-temperature activity of the catalyst is significantly improved. At 175 °C, NO x The conversion rate can reach 80%, which is suitable for the treatment of nitrogen oxides in mobile diesel engine exhaust.
[0015] Furthermore, the loading of metal composite oxides can overcome the low low-temperature catalytic activity of Cu-SSZ-39 itself, improve its low-temperature catalytic activity, and thus have a wide catalytic temperature window. At the same time, it also improves the hydrothermal stability and SO2 tolerance (i.e., resistance to sulfur poisoning) of Cu-SSZ-39.
[0016] Furthermore, the metal composite oxide is loaded onto the surface of Cu-SSZ-39 by an equal volume impregnation method. The specific operation method can be: dissolving the metal precursor in water to obtain a metal precursor solution, uniformly attaching the metal precursor solution to the surface of Cu-SSZ-39, and then drying and calcining, uniformly loading the metal composite oxide on the surface of Cu-SSZ-39, and obtaining a metal composite oxide-loaded Cu-SSZ-39 catalyst.
[0017] Furthermore, the metal composite oxide is uniformly loaded on the surface of Cu-SSZ-39, and the loading method can adopt the method disclosed in the prior art, such as impregnation method, ion exchange method, etc.
[0018] Furthermore, the impregnation method can be: impregnating Cu-SSZ-39 into the metal precursor solution until the loading amount meets the requirements. Experimental verification shows that when the equal volume impregnation method is used, the metal composite oxide can be more evenly dispersed on the surface of Cu-SSZ-39, and the performance is better, so the equal volume impregnation method is preferably used.
[0019] Furthermore, the metal precursor is a soluble salt of a metal, such as a nitrate or acetate. For example, cerium salts are Ce(NO3)3, Ce(CH3COO)3; manganese salts are Mn(NO3)2, Mn(CH3COO)2; and iron salts are Fe(NO3)3, Fe(CH3COO)3.
[0020] Further, the calcination is carried out in a muffle furnace at a calcination temperature of 500-650° C., such as 500° C., 550° C., 600° C., 650° C. Preferably, the calcination time is 1-10 h, such as 1 h, 3 h, 5 h, 8 h, 10 h.
[0021] Further, the loading amount of the metal composite oxide is 1.0 - 10.0 wt.% of the mass of Cu-SSZ-39, for example, 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, 10 wt.%, preferably 5-10 wt.%.
[0022] Furthermore, the Cu-SSZ-39 can be obtained by the method disclosed in the prior art. In Cu-SSZ-39, the loading amount of Cu varies according to the different silicon-aluminum ratios and the different copper loading methods, for example, any value among 1.5%, 2%, 2.5%, 3% and the range therebetween.
[0023] Furthermore, the present invention also provides a metal composite oxide-loaded Cu-SSZ-39 catalyst, which includes Cu-SSZ-39, on which the metal composite oxide is uniformly loaded, and the metal composite oxide is consistent with the above description.
[0024] Furthermore, the loading amount of the metal composite oxide is consistent with that described above.
[0025] Furthermore, in the metal composite oxide-loaded Cu-SSZ-39 catalyst, the loading amount of Cu in Cu-SSZ-39 is 1.5-3 wt.%, for example, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, and 3.0%.
[0026] Furthermore, the metal composite oxide-loaded Cu-SSZ-39 catalyst can be prepared by the method described above, first preparing Cu-SSZ-39, and then uniformly loading the metal composite oxide onto Cu-SSZ-39 in the manner described above.
[0027] Further, in a specific embodiment of the present invention, a preferred method for preparing a metal composite oxide-supported Cu-SSZ-39 catalyst is adopted, and the obtained metal composite oxide-supported Cu-SSZ-39 catalyst has more excellent catalytic performance, and the steps are as follows:
[0028] (1) The commercially available or self-prepared SSZ-39 molecular sieve is placed in an ammonium salt solution, the pH is adjusted with NH3∙H2O and HNO3, and ion exchange is performed at a certain temperature for several hours. The obtained sample is then centrifuged and washed, and dried overnight to obtain NH4-SSZ-39.
[0029] (2) The sample prepared in step (1) was placed in a three-necked flask, and a copper salt solution was added and stirred in a constant temperature water bath for several hours to perform ion exchange. After centrifugal washing and drying, the sample was placed in a tubular furnace for calcination to obtain Cu-SSZ-39.
[0030] (3) The sample prepared in step (2) is placed in a beaker, and the metal precursor solution is slowly added dropwise into the beaker using a pipette under ultrasonic conditions. After being evenly impregnated, the sample is dried overnight and then calcined in a muffle furnace to obtain a metal composite oxide-supported Cu-SSZ-39 catalyst.
[0031] Furthermore, in step (1), the SSZ-39 molecular sieve can be any one of Na-type SSZ-39 and H-type SSZ-39, and the SiO2 / Al2O3 molar ratio is 3.0-40.0.
[0032] Furthermore, in step (1), the ammonium salt is (NH4)2SO4, NH4NO 3、 NH4Cl, solution concentration is 0.1-1.5mol / L, and NH3∙H2O or HNO3 is used to adjust the pH value to 3.6-3.8.
[0033] Furthermore, in step (1), the ion exchange temperature is 60-90 °C, the exchange time is 1-5 h; one or more of deionized water, ethanol or acetone is used for centrifugal washing; and the drying temperature is 70-110 °C.
[0034] Furthermore, in step (2), the copper salt may be CuSO4, Cu(NO3)2, Cu(CH3COO)2, and the solution concentration may be 0.01-1.0 mol / L.
[0035] Furthermore, in step (2), the ion exchange temperature is 25-80 °C, and the exchange time is 1-10 h; one or more of deionized water, ethanol or acetone is used for centrifugal washing; the drying temperature is 70-110 °C; the calcination temperature in the tubular furnace is 550-650 °C, and the calcination time is 1-10 h. The atmosphere is dry air at a flow rate of 50-200 mL / min.
[0036] Furthermore, in step (3), the drying temperature is 70-110 °C; the calcination temperature in the muffle furnace is 500-650 °C, the calcination time is 1-10 h, and the heating rate is 5 °C / min.
[0037] Compared with the prior art, the present invention has the following advantages:
[0038] (1) The present invention significantly improves the low-temperature activity of Cu-SSZ-39 by loading metal composite oxides on it, broadens the catalytic temperature window of the catalyst, and significantly improves the SCR activity of the catalyst. 2+ The sites interact with each other, which can effectively inhibit the aggregation of Cu species during hydrothermal aging and improve its hydrothermal stability.
[0039] (2) The metal composite oxide in the metal composite oxide-loaded Cu-SSZ-39 catalyst of the present invention can act as a SO2 sacrificial agent to protect Cu active species, and thus has a high resistance to SO2 poisoning, is suitable for SCR reaction in the presence of SO2, achieves high NH3-SCR catalytic activity of the catalyst after SO2 poisoning, and has high SO2 tolerance.
[0040] (3) The metal composite oxide-loaded Cu-SSZ-39 catalyst obtained in the present invention has good catalytic activity. The catalyst still maintains good SCR activity after hydrothermal aging and is suitable for eliminating nitrogen oxides in mobile source exhaust gas.
[0041] (4) The preparation method of the present invention is simple and easy to implement, thus reducing the production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments or the prior art are briefly introduced below.
[0043] Figure 1 : This is the X-ray powder diffraction (XRD) pattern of catalyst 8 obtained in Example 3 of the present invention.
[0044] Figure 2The scanning electron microscope (SEM) images of the catalyst 8 obtained in Example 3 of the present invention are shown in Figures a and b. x / Cu-SSZ-39. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0046] Example 1
[0047] 1. Take 2.5g of H-SSZ-39 with a known SiO2 / Al2O3 molar ratio of 17 and place it in a three-necked flask, add 100mL of 0.1 mol / L Cu(NO3)2 solution, stir in a constant temperature water bath at 80 °C for 1 h to perform ion exchange, centrifuge and wash, dry at 105 °C, place in a tube furnace and calcine at 575 °C in a dry air atmosphere for 8 h to obtain Cu-SSZ-39. According to ICP detection, the copper loading is 1.8 wt.%.
[0048] 3. Take a certain amount of Fe(NO3)3 solid and a certain amount of Mn(NO3)2 solution, dissolve them in deionized water at a molar ratio of 1:1, stir for 1 h until they are evenly mixed, and obtain a precursor solution. The concentrations of Fe(NO3)3 and Mn(NO3)2 in the precursor solution are both 0.085 mol / L. Weigh 1g of Cu-SSZ-39 and place it in a beaker. Use a pipette to drop the precursor solution into the beaker under ultrasonic conditions. Use an equal volume impregnation method to load the composite metal oxide onto Cu-SSZ-39. The theoretical loading amount is 1.0wt.% (the loading amount is the ratio of the mass of the composite metal oxide to the mass of Cu-SSZ-39). Similarly, catalysts with loading amounts of 5.0 wt.% and 10.0 wt.% were prepared. Dry at 105 °C overnight, and finally calcine at 550 °C in a muffle furnace for 4 h. After calcination, the nitrate is decomposed to obtain MnFeO x / Cu-SSZ-39 catalysts (wherein the Mn:Fe molar ratio was 1:1), named as Catalyst 1 (loading 1.0 wt.%), Catalyst 2 (loading 5.0 wt.%) and Catalyst 3 (loading 10.0 wt.%).
[0049] The SCR activity of the fresh catalyst prepared above was tested under the following conditions: [NO] = [NH3] = 500 ppm, [O2] = 5.3%, He as the balance gas, total flow rate of 300 mL / min, and space velocity of 100000 h -1 Meanwhile, the Cu-SSZ-39 catalyst without composite metal oxide loading was used as control 1.
[0050] The test results are shown in Table 1.
[0051]
[0052] Example 2
[0053] 1. Take 5g of Na-SSZ-39 with a known SiO2 / Al2O3 molar ratio of 17 and place it in 115mL of 0.3263 mol / L (NH4)2SO4 solution. Use NH3∙H2O or HNO3 to adjust the pH to 3.7. Perform ion exchange at 80 °C for 2 h. Wash the obtained sample by centrifugation and dry it at 105 °C overnight to obtain NH4-SSZ-39.
[0054] 2. Take 2.5g NH4-SSZ-39 and place it in a three-necked flask. Add 100 mL of 0.1 mol / L
[0055] The Cu(CH3COO)2 solution was stirred in a constant temperature water bath at 80 °C for 1 h for ion exchange, washed by centrifugation, dried at 105 °C, and placed in a tube furnace and calcined at 575 °C for 5 h in a dry air atmosphere to obtain Cu-SSZ-39. ICP detection showed that the copper loading was 1.9 wt.%.
[0056] 3. Select any two metal salts of Ce(NO3)3, Mn(NO3)2 and Fe(NO3)3 and three metal salts of CeMnFe, dissolve them in deionized water and stir for 1h until they are evenly mixed, and obtain precursor solutions containing CeMn, CeFe, MnFe and CeMnFe respectively. The concentrations of Ce(NO3)3 and Mn(NO3)2 in the CeMn precursor solution are both 0.27 mol / L, the concentrations of Ce(NO3)3 and Fe(NO3)3 in the CeFe precursor solution are both 0.275 mol / L, the concentrations of Mn(NO3)2 and Fe(NO3)3 in the MnFe precursor solution are both 0.41 mol / L, and the concentrations of Ce(NO3)3, Mn(NO3)2 and Fe(NO3)3 in the CeMnFe precursor solution are all 0.32 mol / L.
[0057] 4. Weigh 1 g of Cu-SSZ-39 and place it in a beaker. Use a pipette to drop the precursor solution into the beaker under ultrasonic conditions. Use an equal volume impregnation method to load the composite metal oxide onto Cu-SSZ-39 with a loading of 5.0 wt.%. Dry at 105 °C overnight and finally calcine at 550 °C in a muffle furnace for 4 h to obtain CeMnO x / Cu-SSZ-39, CeFeO x / Cu-SSZ-39、MnFeO x / Cu-SSZ-39 and CeMnFeO x / Cu-SSZ-39 catalysts (wherein the molar ratios of Ce:Mn, Ce:Fe, and Mn:Fe are all 1:1, Ce:Mn:Fe=1:1:1) were named Catalyst 4, Catalyst 5, Catalyst 6, and Catalyst 7, respectively.
[0058] The SCR activity of the fresh catalyst prepared above was tested under the following conditions: [NO] = [NH3] = 500 ppm, [O2] = 5.3%, He as the balance gas, total flow rate of 300 mL / min, and space velocity of 100000 h -1 Meanwhile, the Cu-SSZ-39 catalyst without supporting the composite metal oxide was used as control 2.
[0059] The fresh catalyst prepared above was subjected to a severe hydrothermal aging treatment, that is, the catalyst was placed in a tubular furnace, the temperature was raised to 800°C at 5°C / min, air containing 10% water vapor by volume was introduced, and the temperature was kept for 16 hours. The catalyst after hydrothermal aging was tested for SCR activity under the same test conditions as above. At the same time, the Cu-SSZ-39 catalyst without composite metal oxide loading was used as control 2.
[0060] The test results are shown in Table 2 and Table 3.
[0061]
[0062] Example 3
[0063] 1. Take 5g of Na-SSZ-39 with a known SiO2 / Al2O3 molar ratio of 17 and place it in 115mL of 0.3263 mol / L (NH4)2SO4 solution. Use NH3∙H2O or HNO3 to adjust the pH to 3.7. Perform ion exchange at 80 °C for 2 h. Wash the obtained sample by centrifugation and dry it at 105 °C overnight to obtain NH4-SSZ-39.
[0064] 2. Take 2.5g NH4-SSZ-39 and place it in a three-necked flask. Add 100 mL of 0.1 mol / L
[0065] The CuSO4 solution was stirred in a constant temperature water bath at 80 °C for 1 h for ion exchange, washed by centrifugation, dried at 105 °C, and placed in a tube furnace and calcined at 575 °C for 8 h in a dry air atmosphere to obtain Cu-SSZ-39. The ICP test showed that the copper loading was 1.7 wt.%.
[0066] 3. Take a certain amount of Ce(NO3)3 solid, Fe(NO3)3 solid and a certain amount of Mn(NO3)2 solution, dissolve them in deionized water and stir for 1 h until they are evenly mixed to obtain a precursor solution, in which the molar ratio of Ce:Mn:Fe is 6:2:2, the concentration of Ce(NO3)3 is 0.372 mol / L, the concentration of Mn(NO3)2 is 0.213 mol / L, and the concentration of Fe(NO3)3 is 0.195 mol / L.
[0067] 4. The composite metal oxide was loaded onto Cu-SSZ-39 by the equal volume impregnation method according to the theoretical loading amount of 5.0 wt.% (the loading amount is the ratio of the mass of the composite metal oxide to the mass of Cu-SSZ-39). The specific operation is as follows: 1 g of Cu-SSZ-39 was weighed and placed in a beaker. 1440 μl of the precursor solution was added dropwise to the beaker with a pipette under ultrasonic conditions. Then, ultrasonic dispersion was performed for 15 min until the impregnation was uniform. The mixture was dried at 105 °C overnight and finally calcined at 550 °C in a muffle furnace for 4 h to obtain CeMnFeO with a Ce:Mn:Fe molar ratio of 6:2:2. x / Cu-SSZ-39 catalyst, named as catalyst 8.
[0068] Figure 1 This is the XRD diagram of catalyst 8. It can be seen from the figure that the impregnation process does not change the framework structure of the molecular sieve. Figure 2 This is the SEM picture of Cu-SSZ-39 before and after loading the composite metal oxide. It can be seen from the picture that the microscopic morphology of the molecular sieve does not change after loading the composite metal oxide.
[0069] The catalyst was subjected to an SCR activity test and a sulfur resistance test, wherein the SCR activity test conditions were consistent with those in Example 2, and the sulfur resistance test conditions were: [NO] = [NH3] = 500 ppm, [SO2] = 50 ppm, [O2] = 5.3%, He as the balance gas, a total flow rate of 300 mL / min, and an air velocity of 100000 h -1 Meanwhile, the Cu-SSZ-39 catalyst without composite metal oxide loading was used as control 3.
[0070] The test results are shown in Tables 4 and 5.
[0071]
[0072] Example 4
[0073] 1. Cu-SSZ-39 was prepared according to the method of Example 3.
[0074] 2. Take a certain amount of Ce(NO3)3 solid, Fe(NO3)3 solid and a certain amount of Mn(NO3)2 solution, dissolve them in deionized water and stir for 1 h until they are evenly mixed to obtain a precursor solution, in which the molar ratios of Ce:Mn:Fe are 2:2:6 and 2:6:2, respectively. When the molar ratio is 2:2:6, the concentration of Ce(NO3)3 is 0.190 mol / L, the concentration of Mn(NO3)2 is 0.213 mol / L, and the concentration of Fe(NO3)3 is 0.382 mol / L. When the molar ratio is 2:6:2, the concentration of Ce(NO3)3 is 0.190 mol / L, the concentration of Mn(NO3)2 is 0.395 mol / L, and the concentration of Fe(NO3)3 is 0.192 mol / L.
[0075] 3. Weigh 1g Cu-SSZ-39 and place it in a beaker. Use a pipette to drop the precursor solution into the beaker under ultrasonic conditions. Use an equal volume impregnation method to load the composite metal oxide onto Cu-SSZ-39 with a loading of 5.0 wt.%. Dry overnight at 105°C and finally calcine at 550°C in a muffle furnace for 4 h. CeMnFeO with a Ce:Mn:Fe molar ratio of 2:2:6 and 2:6:2 was obtained. x / Cu-SSZ-39 catalysts, named as Catalyst 9 and Catalyst 10 respectively.
[0076] The SCR activity of the above catalysts was tested under the following conditions: [NO] = [NH3] = 500 ppm, [O2] = 5.3%, He as the balance gas, total flow rate of 300 mL / min, and space velocity of 100000 h -1 Meanwhile, catalyst 8 was used as a control.
[0077] The test results are shown in Table 6.
[0078]
[0079] From the above, it can be seen that when the molar ratio of Ce:Mn:Fe is 6:2:2 and 1:1:1 respectively, the low-temperature and high-temperature SCR catalytic performance of the catalyst is better, while when the molar ratio is 2:6:2, the high-temperature performance is sharply reduced because the manganese addition amount is too high.
[0080] Comparative Example 1
[0081] 1. Cu-SSZ-39 was prepared according to the method of Example 3.
[0082] 2. Take a certain amount of Ce(NO3)3 solid, Fe(NO3)3 solid and a certain amount of Mn(NO3)2 solution, dissolve them in deionized water and stir for 1 h until they are completely dissolved to obtain a Ce precursor solution with a concentration of 0.202 mol / L, a Fe precursor solution with a concentration of 0.217 mol / L, and a Mn precursor solution with a concentration of 0.4 mol / L.
[0083] 3. Weigh 1g of Cu-SSZ-39 and place it in a beaker. Use a pipette to drop the precursor solution into the beaker under ultrasonic conditions. Use an equal volume impregnation method to load the composite metal oxide onto Cu-SSZ-39 with a loading of 5.0 wt.%, dry it overnight at 105°C, and finally calcine it at 550°C in a muffle furnace for 4 h. CeO2 / Cu-SSZ-39, MnO2 / Cu-SSZ-39, and Fe2O3 / Cu-SSZ-39 catalysts were obtained, named catalyst 11, catalyst 12, and catalyst 13, respectively.
[0084] The SCR activity of the above catalysts was tested under the following conditions: [NO] = [NH3] = 500 ppm, [O2] = 5.3%, He as the balance gas, total flow rate of 300 mL / min, and space velocity of 100000 h -1 Meanwhile, control 3 was used as a control.
[0085] The test results are shown in Table 7.
[0086]
[0087] It can be seen from the above table that the low-temperature activity of Cu-SSZ-39 is improved only by modifying it with CeO2 or Fe2O3, among which the improvement effect of CeO2 is higher than that of Fe2O3. When Cu-SSZ-39 is modified only with MnO2, although the low-temperature activity is significantly improved, the non-selective oxidation of NH3 is serious after 400 °C due to the presence of Mn, and the activity drops sharply.
[0088] Comparative Example 2
[0089] 1. Cu-SSZ-39 was prepared according to the method of Example 3.
[0090] 2. Select any two metal salts of Y(NO3)3, Zr(NO3)4 and Cr(NO3)3 and three metal salts of YZrCr, dissolve them in deionized water and stir for 1h until they are evenly mixed, and obtain precursor solutions containing YZr, YCr, ZrCr and YZrCr respectively. The concentrations of Y(NO3)3 and Zr(NO3)4 in the YZr precursor solution are both 0.294 mol / L, the concentrations of Y(NO3)3 and Cr(NO3)3 in the YCr precursor solution are both 0.353 mol / L, the concentrations of Zr(NO3)4 and Cr(NO3)3 in the ZrCr precursor solution are both 0.335 mol / L, and the concentrations of Y(NO3)3, Zr(NO3)4 and Cr(NO3)3 in the YZrCr precursor solution are all 0.328 mol / L.
[0091] 3. Weigh 1 g of Cu-SSZ-39 and place it in a beaker. Use a pipette to drop the precursor solution into the beaker under ultrasonic conditions. Use an equal volume impregnation method to load the composite metal oxide onto Cu-SSZ-39 with a loading of 5.0 wt.%. Dry at 105 °C overnight and finally calcine at 550 °C in a muffle furnace for 4 h to obtain YZrO x / Cu-SSZ-39, YCrO x / Cu-SSZ-39, ZrCrO x / Cu-SSZ-39, YZrCrO x / Cu-SSZ-39 catalysts (wherein the molar ratios of Y:Zr, Y:Cr, and Zr:Cr are all 1:1, and the molar ratio of Y:Zr:Cr is 1:1:1) are named catalyst 14, catalyst 15, catalyst 16, and catalyst 17, respectively.
[0092] The SCR activity of the fresh catalyst prepared above was tested under the following conditions: [NO] = [NH3] = 500 ppm, [O2] = 5.3%, He as the balance gas, total flow rate of 300 mL / min, and space velocity of 100000 h -1 Meanwhile, control 3 was used as a control.
[0093] The test results are shown in Table 8.
[0094]
[0095] From the above, it can be seen that not any metal oxide can improve the catalytic performance of Cu-SSZ-39. Loading some metal oxides not only cannot improve the catalytic performance, but also reduce the activity. This is because these metal oxides cover the active sites and do not have good redox properties, resulting in a decrease in catalyst activity. The present invention selects any 2 or 3 composite oxides of CeMnFe to be introduced into Cu-SSZ-39 through experimental screening, which not only does not reduce the catalytic activity of the catalyst, but also improves its low-temperature catalytic performance, stabilizes its high-temperature catalytic performance, and widens the catalytic temperature window of the catalyst. At the same time, the hydrothermal stability and sulfur poisoning resistance of the catalyst are also effectively improved.
[0096] It can be seen from the above experiments that when introducing composite metal oxides of Ce, Mn and Fe to modify Cu-SSZ-39, the ratio of the three metals Ce, Mn and Fe should be appropriate. When the ratio of Mn is too high, NH3 non-selective oxidation is serious and the activity drops sharply above 400 °C; when the ratio of Fe is too high, the activity improvement in the low temperature section is not obvious.
[0097] From the above experiments, it can be seen that the composite metal oxide CeMnFeO x Evenly dispersed on the surface of Cu-SSZ-39 molecular sieve, CeMnFeO x Ce, Mn, and Fe have a synergistic effect. The addition of composite metal oxides improves the redox performance and surface acidity of Cu-SSZ-39, thereby improving the SCR activity of Cu-SSZ-39 catalyst. x There is interaction between them and Cu, which inhibits the aggregation of Cu species during hydrothermal aging, thereby improving the hydrothermal stability.
[0098] The Cu-SSZ-39 loaded composite metal oxide catalyst prepared by the invention has excellent NH3-SCR catalytic activity and hydrothermal aging resistance and improves SO2 tolerance.
[0099] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for improving the performance of Cu-SSZ-39, characterized in that: A metal composite oxide is loaded onto the surface of Cu-SSZ-39 to improve the NH3-SCR catalytic activity, hydrothermal stability and SO2 tolerance of Cu-SSZ-39. The metals in the metal composite oxide are cerium, manganese and iron. The molar ratio of cerium, manganese and iron is 3:1:
1. The loading amount of the metal composite oxide is 5 wt.% of the mass of Cu-SSZ-39.
2. The method according to claim 1, characterized in that: The metal composite oxides are uniformly loaded on the surface of Cu-SSZ-39.
3. The method according to claim 2, characterized in that: The loading method of the metal composite oxide is as follows: dissolving the metal precursor in water to obtain a metal precursor solution, uniformly attaching the metal precursor solution to the surface of Cu-SSZ-39 by an equal volume impregnation method, and then drying and calcining to uniformly load the metal composite oxide on the surface of Cu-SSZ-39.
4. The method according to claim 3, characterized in that: The metal precursor is a nitrate or acetate of the metal.
5. The method according to claim 3, characterized in that: The calcination is carried out in a muffle furnace at a temperature of 500-650 °C.
6. The method according to claim 3 or 5, characterized in that: The calcination time is 1-10 h.
7. A metal composite oxide supported Cu-SSZ-39 catalyst, characterized in that: The invention comprises Cu-SSZ-39, on which a metal composite oxide is uniformly loaded. The metals in the metal composite oxide are cerium, manganese and iron, the molar ratio of cerium, manganese and iron is 3:1:1, and the loading amount of the metal composite oxide is 5wt.% of the mass of Cu-SSZ-39.
8. The metal composite oxide supported Cu-SSZ-39 catalyst according to claim 7, characterized in that: The loading amount of Cu in Cu-SSZ-39 is 1.5-3 wt.%.
Citation Information
Patent Citations
A Cu-SSZ-39@SSZ-39 core-shell molecular sieve, its preparation method and application
CN112299436B
Cu-SSZ-39@Cu-SSZ-13 composite molecular sieve with core-shell structure and its synthesis method
CN112958148B
Preparation method and application of auxiliary agent doped Cu-SSZ-39 catalyst
CN106925341A